Granulocyte transfusion combined with granulocyte colony stimulating factor in severe infection patients with severe aplastic anemia: a single center experience from China. - Huaquan Wang; Yuhong Wu; Rong Fu; Wen Qu; Erbao Ruan; Guojin Wang; Hong Liu; Jia Song; Limin Xing; Jing Guan; Lijuan Li; Chunyan Liu; et al. (PLoS ONE, 2014)
OBJECTIVE: To investigate the efficacy and safety of granulocyte transfusion combined with granulocyte colony stimulating factor (G-CSF) in severe infection patients with severe aplastic anemia (SAA). METHODS: Fifty-six patients in severe infections with SAA who had received granulocyte transfusions combined with G-CSF from 2006 to 2012 in our department were analyzed. A retrospective analysis was undertaken to investigate the survival rates (at 30 days, 90 days and 180 days), the responses to treatment (at 7 days and 30 days, including microbiological, radiographic and clinical responses), the neutrophil count and adverse events after transfusion. RESULTS: All SAA patients with severe infections were treated with granulocyte transfusions combined with G-CSF. Forty-seven patients had received antithymocyte globulin/antilymphocyte globulin and cyclosporine A as immunosuppressive therapy. The median number of granulocyte components transfused was 18 (range, 3-75). The survival at 30 days, 90 days and 180 days were 50(89%), 39(70%) and 37(66%) respectively. Among 31 patients who had invasive fungal infections, the survival at 30 days, 90 days and 180 days were 27(87%), 18(58%) and 16(52%) respectively. Among the 25 patients who had refractory severe bacterial infections, the survival at 30 days, 90 days and 180 days were 23(92%), 21(84%) and 21(84%) respectively. Survival rate was correlated with hematopoietic recovery. Responses of patients at 7 and 30 days were correlated with survival rate. Common adverse effects of granulocyte transfusion included mild to moderate fever, chills, allergy and dyspnea. CONCLUSION: Granulocyte transfusions combined with G-CSF could be an adjunctive therapy for treating severe infections of patients with SAA.